Sexuality: Actions and Representations from APAE's Self-determination and Self-advocacy Movement - Chagas, Patricia Monteiro Lima (2023)
The purpose of this article is to carry out an integrative review of studies published by the Self-determination and Self-advocacy Movement of the Association of parents and friends of people with disabilities (APAE) Brazil, related to sexuality, identifying the theme in the different records released over the years. Magazines, projects, booklets and guiding documents that address the themes were found. The question that guided the study was to understand the discussions about sexuality in the face of the self-determination and self-advocacy movement, which may serve the (re)construction of critical thinking and the development of policies, protocols, resources, programs and procedures that contribute to the discussion and understanding of sexuality. From the survey of five thematic categories, it was possible to identify discussions about sexuality, sex, gender and sexual relationship, safety, abuse, affective life, dating and marriage, sexual rights, masturbation and prejudice. The studies highlight the importance of bringing to the center of debates the perceptions of society and families, sexuality education and the right of people with disabilities to express themselves and experience their sexuality, in a continuous process throughout their lives.